Diseño de guía para inspección de taladros de perforación petrolera y equipos asociados de acuerdo con la norma NFPA 70e 2018 para la empresa Guias Group S.A.S. (2020)
The company GIAS GROUP SAS is located in the north of the city of Bogotá DC, it exercises its activities in the provision of consulting and interventory services in occupational health, industrial safety, environmental management and engineering for the oil, energy, forestry, road and industrial. Given the innovation and updating in the national and international regulations, the need arises for GIAS GROUP S.A.S to design a validation tool that facilitates the work when carrying out inspections of oil drilling drills and associated equipment under the NFPA 70E 2018 standard. One of the problems presented by the company is the amount of time required in the execution of audits, to consult procedures and verification of the electrical systems of equipment for oil drilling; therefore, the use of this tool will improve inspection times in the different client companies of GIAS GROUP S.A.S, and it will be a single procedure, it will also have help for electrical calculations and conversion of different units. The latest version of the NFPA 70E 2018 standard will be interpreted, in order to carry out the design of the tool and apply it in the inspection guide, complying with international guidelines along with current Colombian regulations on electrical safety.